1976
DOI: 10.1002/kin.550080609
|View full text |Cite
|
Sign up to set email alerts
|

Some reactions of the isopropyl radical

Abstract: The decomposition of ethane sensitized by isopropgl radicals was studied in the tempera-The rate of formation of n-butane, isopentane, and 2,S-dimethyl-t,iire range of 496-548°K. butane were nieasrued. The expression kI/PZ1'* was found to be log kl/kg"2(dm3'*/n~ol"2 . see1!*) = (3.2 f 0.4) -(54 f 3 kJ/mol)/2.3RTwhere k , and k 2 are rate constants ofThe decomposition of propylene sensitized by isopropgl radicals was studied between 494 The :end 580'K by determination of the initial rates of formation of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The isobutyl case is illustrated in Scheme where both reactions R1b and R1c lead to isobutene and H. While we will argue later that the 1,2 H shift in isobutyl is unimportant, it cannot be distinguished from direct C–H scission based on the end products. Studies in the literature of C–H bond scission , and 1,2 H shifts ,, have yielded conflicting results, and this literature will be briefly reviewed in the discussion section and compared to our results. , …”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…The isobutyl case is illustrated in Scheme where both reactions R1b and R1c lead to isobutene and H. While we will argue later that the 1,2 H shift in isobutyl is unimportant, it cannot be distinguished from direct C–H scission based on the end products. Studies in the literature of C–H bond scission , and 1,2 H shifts ,, have yielded conflicting results, and this literature will be briefly reviewed in the discussion section and compared to our results. , …”
Section: Introductionmentioning
confidence: 70%
“…In a series of papers from the 1960s on strategically deuterated, isopropyl and isobutyl radicals, Jackson and McNesby set upper limits on the amount of 1,2 H-shifts and C–H β-scission at (472 to 813) K of 7% for isopropyl and 1% for isobutyl and argued that these upper limits were lower than other literature values because their experiments were free from nonthermal photochemistry . Multiple other researchers claimed significant 1,2 H-shift branching ratios for decades afterward. ,, These claims were usually based, however, on the detection of compounds that could easily be produced from side chemistry, including methane and ethene. , …”
Section: Discussionmentioning
confidence: 99%
“…Under the analytical conditions reported by Szirovicza and Marta [51, DMB and 2-methylpentane can not be separated. In the presence of propylene, however, the two substances are formed in comparable amounts, which were measured jointly in [5]. It follows from the rate constant expression that with the increase of the quantity of DMB values lower than the probable ones are obtained for the Arrhenius parameters of kls.…”
Section: Variation Of Relative Pressure Of Isobutene At 5% Conversionmentioning
confidence: 70%
“…Analyzing the kinetic results available for the isomerization of isopropyl radicals it can be concluded that with two exceptions the rate constant data are within a factor of about 10. The results originated from the pyrolysis of azoisopropane are higher by more than two orders of magnitude than the lowest rate constant [8]. This discrepancy can be explained by the assumption that azoisopropane had some n -C3H7 contamination (for instance, nX3H7-N = N -~s o -C~H~, which is difficult to detect in excess of azoisopropane).…”
Section: Discussionmentioning
confidence: 95%